Foreign Influence on Ottoman Miniatures in the Context of Selected Examples - Aslan, Halide; Akter, Farjana (CenRaPS Journal of Social Sciences, 2024)
Ottoman miniature art has an important place in Islamic miniature art. For nearly three hundred years under the supervision of the Ottoman sultans, the palace nakkashane produced the most valuable works of Turkish miniature art. Art-loving Ottoman sultans patronized both local and foreign artists in the workshop. Therefore, with the joint efforts of artists who mastered different styles, Ottoman miniature art came into the era of extreme progress of Turkish miniature art. It is noteworthy that there was foreign influence on Ottoman painting but it never retained ownership of Ottoman painting. Although the Ottoman Empire gained such richness in miniature but the strong influence of external elements was proven. In this article, it has been examined in order to identify the foreign characteristics that influenced Ottoman miniature art. Apart from the miniatures used as samples in the research, many Ottoman miniatures which contain foreign influences were also examined to identified similar and different aspects. In this way the data and results were generated and strengthened.